THE EXERCISE OF THE RIGHT TO LEGAL PERSONS AND COLLECTIVE PROPERTY OF THE LAND OF INDIGENOUS PEOPLES IN PERU. ANALYSIS MADE BASED ON THE SITUATION OF 14 COMMUNITIES IN THE DEPARTMENT OF LORETO - González Watson, Ana María (2019)
The author critically exposes the problem that exists in the norms that regulate the procedures for the recognition and registration of legal status and the effective exercise of the native communities that still exist in the country. In addition, it aims to determine that, in this area, despite the fact that the State has ratified international commitments on the recognition, protection and promotion of the rights of indigenous peoples, in cases where communities are unable to register their titles by an overlap, caused even by the same State, ignore fundamental norms of administrative law, unnecessarily harming these populations that are among the most vulnerable, omitting their obligation to protect them. It also has the purpose of verifying the need for mechanisms to be established that safeguard the ownership of the lands of the communities during the years it takes the State to recognize and title a community. Finally, the author concludes that the State is not guaranteeing in practice the recognition and the right to property of these populations and that not only changes in current legislation are necessary but that it is essential to develop a public policy that includes sustainable productive projects that are raised with an intercultural approach, that is, recognizing the intrinsic interdependence relationship between the communities and the natural resources that surround them as well as the diversified character in their subsistence activities that are part of their culture.